Molecular profiling-based decision for targeted therapies in IDH wild-type glioblastoma. Issue 1 (22nd January 2020) - Kessler, Tobias; Berberich, Anne; Casalini, Belen; Drüschler, Katharina; Ostermann, Hannah; Dormann, Andrea; Walter, Sandy; Hai, Ling; Schlesner, Matthias; Herold-Mende, Christel; Jungk, Christine; Unterberg, Andreas; et al.
Abstract: Background: Molecular profiling allows tumor classification as well as assessment of diagnostic, prognostic, and treatment-related molecular changes. Translation into clinical practice and relevance for patients has not been demonstrated yet. Methods: We analyzed clinical and molecular data of isocitrate dehydrogenase wild-type glioblastoma patients with sufficient clinical follow-up from the Heidelberg Neuro-Oncology Center and with molecular analysis of tumor tissue that consisted of DNA methylation array data, genome-scale copy number variations, gene panel sequencing, and partly mTOR immunohistochemistry between October 2014 and April 2018. Results: Of 536 patients screened, molecular assessment was performed in 253 patients (47%) in a prospective routine clinical setting with further clinical appointments. Therapy decision was directly based on the molecular assessment in 97 (38%) patients. Of these, genetic information from MGMT ( n  = 68), EGFR ( n  = 7), CDKN2A/B ( n  = 8), alterations of the PI3K–AKT–mTOR pathway ( n  = 5), and BRAF ( n  = 3) have been the most frequently used for decision making with a positive overall survival signal for patients with glioblastoma harboring an unmethylated MGMT promoter treated according to the molecular assignment. Based on detected molecular alterations and possible targeted therapies, we generated an automated web-based prioritization algorithm. Conclusion: Molecular decision making in clinical practice was mainly driven by MGMT promoter status in elderly patients and study inclusion criteria. A reasonable number of patients have been treated based on other molecular aberrations. This study prepares for complex molecular decisions in a routine clinical decision making.